Development of national tennis player value chain structure: statistical analysis of tennis player pathway - Cakravastia, A.; Yudhistira, T.; Ameera, A.; Setiawan, M. (Coaching and Sport Science Review, 2023)
Creating a system of tennis player development to establish and sustain a nation's competitive performance is a problem faced by many countries. This research attempts to implement the value chain structure of tennis player development and the tennis player pathway developed by Cakravastia and Setiawan (2022). This paper develops a partial least squares model by analysing the data of 41 countries from the ITF Global Report (2021). The results of this study identify Total tennis coaches and Total tennis courts in a country have a significant effect on the number of total tennis players in that country. This study confirmed there is a significant relationship between the total number of tennis players, the total number of junior players, the total number of pro players, and the total number of players representing a country in the Grand Slam main draw.